Innovative Methods For Managing Business Processes in the Digital Economy - GUSEVA, O.; POKANEVYCH, Y. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
The article analyzes and outlines innovative methods of managing business processes of enterprises in the minds of the rapid development of the digital economy. The key determinants of strategic changes in the economy have been identified. These include: the exponential growth of obligations and the diversity of data, which is an attribute of the digital economy; platformization and edge effects; democratization of innovation based on open platforms, crowdsourcing and edge models; digital technologies that promote the clarity of the functioning of enterprises. It has been established that these determinants form a clearly new reality of the functioning of enterprises and require updated methods of managing business processes in accordance with the specifics of digital transformation. The latest technologies that accelerate digital transformation in managing business processes of enterprises have been identified. It is clear that a key aspect of digital transformation is flexibility. In the minds of the digital environment, which is rapidly changing, business is required to develop innovative methods of managing business processes to quickly respond to changing market trends and technological innovations. Digital methodologies that include iterative development and strategic management of business processes are an important factor in maintaining a competitive advantage in the digital economy. It has been established that innovative methods of business process management lie in the promotion of new ideas, technologies, models and practical approaches for optimization and reduction of essential business processes that allow you to increase efficiency, optimize costs and improve the quality of products and services. Innovative methods include such methods as innovative reengineering, Scrum, Agile, PDSA, Sipok, continuous upgrading and development of specialized BPM systems for modeling and analysis of business processes.